Immunoglobulin a nephropathy: a 10-year analysis in a single Malaysian centre - Aminat, Suleman-Alabi; Abd Ghani, Fauzah; Zakaria, Nor Fadhlina; Osman, Malina; Hod, Rafidah (Universiti Putra Malaysia, 2023)
Introduction: Immunoglobulin A nephropathy (IgAN), also referred to as Berger’s disease, is the leading primary glomerular disease cause of end-stage kidney disease (ESKD). Its prevalence, presentation, and progression have been shown to vary between different regions and ethnicities. This study aims to explore the presentation, predictors of disease progression, and outcome in a cohort of Malaysian patients with IgAN. Methods: This study evaluated retrospective data from 82 patients with renal biopsy-proven IgAN. The patients were classified into two categories based on their estimated glomerular filtration rate (eGFR) at the last follow-up: those with progressive disease (50% reduction in eGFR from the time of biopsy and/or eGFR <15 ml/min/1.73 m2) and those with non-progressive disease. Results: The majority of patients (75.6%) were female and, 47.6% were less than 30 years old at the time of the renal biopsy. The most common clinical presentation was proteinuria (86.4%). At the end of a median follow-up of 2.7 (IQR 1.2-5.1) years, 29.3% of patients reached the combined renal outcome. Males were more likely than females to have progressive disease (OR = 2.89). The survival rates without ESKD at five and ten years are 82% and 78%, respectively. Multivariate cox regression analysis showed MAP (HR =1.05 95% CI 1.01-1.10), UPCI (HR=13.67 95%CI 1.06-175.88), and MESTC score >3 (HR=3.95 95%CI 1.09-14.23) as predictors of the combined renal outcome. Conclusion: IgAN is not a benign disease, with a significant progression to ESKD in this cohort. MAP, UPCI, and MESTC >3 are predictors of disease progression.